1999
DOI: 10.1111/j.1911-3846.1999.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Differences in Audit Workpaper Review Performance*

Abstract: This paper investigates the performance of senior and staff auditors in the identification of conceptual and mechanical errors during workpaper review. In this study, we begin to examine the potential for effectiveness and efficiency gains by involving staff (assistant) auditors in the review process. We find that senior auditors were more accurate than staff auditors in identifying conceptual errors contained in a hypothetical set of workpapers just reviewed. However, staff auditors were more accurate than se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
5
29
0
2
Order By: Relevance
“…Research subsequent to Ramsay (1994) and Harding and Trotman (1999) has found no effectiveness (Bamber and Ramsay, 1997) or efficiency (Bamber and Ramsay, 2000) gains from specifically directing managers and seniors to focus on the types of errors for which they have a comparative advantage in identifying. One difficulty in attempting to improve review effectiveness and efficiency in light of the findings of Ramsay (1994) and Harding and Trotman (1999) is a limited understanding of precisely how knowledge structures differ across hierarchical levels and the relationship between different knowledge structures and review performance.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Research subsequent to Ramsay (1994) and Harding and Trotman (1999) has found no effectiveness (Bamber and Ramsay, 1997) or efficiency (Bamber and Ramsay, 2000) gains from specifically directing managers and seniors to focus on the types of errors for which they have a comparative advantage in identifying. One difficulty in attempting to improve review effectiveness and efficiency in light of the findings of Ramsay (1994) and Harding and Trotman (1999) is a limited understanding of precisely how knowledge structures differ across hierarchical levels and the relationship between different knowledge structures and review performance.…”
Section: Introductionmentioning
confidence: 95%
“…In doing so, it examines a theoretically significant, but previously unexplored aspect of workpaper reviewer expertise, namely knowledge structure. It refocusses research effort directed towards using the findings of Ramsay (1994) and Harding and Trotman (1999) to improve review effectiveness and efficiency.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because most of the interactions among audit team members occur within the review process, many of the systematic differences between auditors come into play in this process. For example, Ramsay (1994) and Harding and Trotman (1999) provide evidence of between-reviewer variance attributable to knowledge differences. It seems likely that at least some of these auditor characteristics would affect the openness with which knowledge is shared in conducting the audit.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Just as knowledge sharing among employees can increase organizational effectiveness, it can enhance the effectiveness, efficiency and integrity of the audit process in formulating the most appropriate audit opinion (Vera-Muñoz et al, 2006;1 In the specific case of audit engagements, individual members of the audit team typically perform only a discrete part of the audit process, such that knowledge about the client environment, industry, and interactions with the client's operations is unevenly distributed among members of the audit team (Murthy and Kerr, 2004;Harding and Trotman, 1999). Compounding this uneven distribution of knowledge, audit firms are increasingly adopting a more holistic "top down" methodology-based on obtaining an in-depth understanding of clients' business strategies and processes (e.g.…”
Section: Introduction and Overviewmentioning
confidence: 99%